Proceso de atención al cliente en Agroservicio Villacrés - Fajardo Barbera, Evelyn Lizbeth (2021)
The case study is carried out on the "Agroservicio Villacres" which is an SME with extensive business experience in the local market of the city of Babahoyo; place where important internal weaknesses have been identified in organizational management, which condition the user service process. The objective of the research is to analyze the user service process, where the main conditioning variables are studied, such as: empirical administrative management, weak inventory control, credit sales, sufficient human talent and work profile. The methodology has a descriptive scope, since each of the findings identified in the analysis are described. The methods used are deductive and inductive with the types of field and documentary research. While the techniques used were surveys and interviews, which allowed the following results to be obtained: The customer service process is conditioned by empirical administrative management, inventory management is not used that helps to have a safety stock and respond adequately the changes that occur in the consumer market. The “Agroservicio Villacres” carries out credit sales where customers do not respect the agreed times for the payment of installments, which has generated liquidity problems due to inadequate collection management and technology and information tools are not used to establish channels much more effective communication with customers; In other words, the application of digital marketing is ignored.